Solomon Islands : Tax Summary and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
This Tax Summary and Statistical Appendix for the Solomon Islands outlines the summary of various taxes. Residents are taxed on their worldwide income. Nonresidents are taxed on income sourced from the Solomon Islands. Both resident and nonresident investors undertaking commercial, economic, industrial or professional activity in the Solomon Islands may apply to the Commissioner of Inland Revenue for an exemption from income tax. An excise duty is levied on plugs, twist, fig, stick, cake, and coarse cut tobacco, and on beer and cigarettes produced in the Solomon Islands.